Melanoma within nevus spilus. - Tagliavanti, M.; Pirrelli, M. (European Journal of Pediatric Dermatology, 2016)
Nevus spilus (NS) is a usually hypermelanic area of skin where insist congenital or acquired nevi with higher density than the surrounding normal skin; the hypermelanic stain is often apparently acquired; however, its considerable extension when it appears and its progressive pigmentation suggest that at birth the background stain is already determined, although not clinically obvious (2). Within NS melanoma (M) may develop as within whatever melanocytic nevus, but its incidence is of 0.13 to 0.2% of cases and the average age of onset is 49 years (1), then not significantly different from data of M in the population without NS. The localization of the NS is not relevant to the onset of M, while a risk factor seems to be the extension of NS because in 87% of cases of NS complicated by melanoma the diameter of NS is greater than 4 cm and no M arose on NS less than 1.3 cm large.